Storage of Terminalia Barks in the Open-its Effect on Oxalic Acid& Tannin Content - Bhatia, Kuldip; Lal, Jia; Swaleh, Mohd (Indian Forester, 1981)
The barks of Terminalia species are a good source of Oxalic acid and Tannins. On storing these barks in the open to stand a rainfall of 2825.80 mm the Oxalic acid content remained almost unaffected. The Tannins in these barks were leached out.